Indocyanine green based fluorescent polymeric nanoprobes for in vitro imaging - YILMAZ, BETÜL; OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN (WILEY, 2020)
Indocyanine green (ICG) provides an advantage in the imaging of deep tumors as it can reach deeper location without being absorbed in the upper layers of biological tissues in the wavelengths, which named therapeutic window in the tissue engineering. Unfortunately, rapid elimination and short-term stability in aqueous media limited its use as a fluorescence probe for the early detection of cancerous tissue. In this study, stabilization of ICG was performed by encapsulating ICG molecules into the biodegradable polymer composited with poly(l-lactic acid) and poly(epsilon-caprolactone) via a simple one-step multiaxial electrospinning method. Different types of coaxial and triaxial structure groups were performed and compared with single polymer only groups. Confocal microscopy was used to image the encapsulated ICG (1 mg/mL) within electrospun nanofibers and in vitro ICG uptake by MIA PaCa-2 pancreatic cancer cells. Stability of encapsulated ICG is demonstrated by the in vitro sustainable release profile in PBS (pH = 4 and 7) up to 21 days. These results suggest the potential of the ability of internalization and accommodation of ICG into the pancreatic cell cytoplasm from in vitro implanted ICG-encapsulated multiaxial nanofiber mats. ICG-encapsulated multilayer nanofibers may be promising for the local sustained delivery system to eliminate loss of dosage caused by direct injection of ICG-loaded nanoparticles in systemic administration.
Keywords: controlled release; encapsulation; indocyanine green; multiaxial electrospinning; near-infrared nanoprobe; CONTROLLED-RELEASE; DRUG-DELIVERY; NANOPARTICLES; NANOFIBERS; ENCAPSULATION; PEG; CELLULOSE; OXIDE; ICG